Resolving tensions: optimising the role of primary care in lung cancer follow-up care. (1st April 2011) - Highet, G; Murray, S A; Campbell, C; Kendall, M; Rainey, P; Neal, R; Rose, P; Anandan, C; Amoakwa, E; Weller, D
Abstract : Abstract: Introduction: There is a little consensus on how to manage the supportive and palliative care needs of people with lung cancer once they have completed initial treatment. We aimed to gain insights into the perspectives of clinicians and service users as to how primary care could provide better care in collaboration with lung cancer specialists. Methods: We conducted a qualitative study encompassing (a) telephone interviews (84) with healthcare professionals from four UK healthcare authorities, recruited through primary care research networks and other professional contacts and working in primary, secondary and palliative care, and (b) focus groups (4) with lung cancer patients and carers recruited through the Roy Castle Foundation. Interviews and focus groups were digitally recorded, transcribed and entered into NVivo for thematic analysis, initially from different perspectives and then synthesised across the whole data set. Results: Lung cancer care is currently 'shared' rather than 'integrated' across heath care sectors. Debates about follow-up care tend to make a distinction between clinical care (provided in hospital by specialists) and supportive care (provided in the community by generalists) and there are contested ideas about where best to follow-up lung cancer patients who are relatively 'stable'. Psycho-social support, support for carers and communication between primary and secondary care were identified as potential areas for development. Conclusion: Lung cancer follow-up care is characterised by a range of tensions which must be resolved if primary care is to play an optimum role in providing follow-up care and support for lung cancer patients and their carers.